TUBUH IDEAL DAN DISIPLIN SOSIAL: ANALISIS FOUCAULDIAN TERHADAP STANDAR ESTETIKA KOREA DALAM BUDAYA POPULER INDONESIA - Alfian Fadhilah; Muthiullah; Ayyesa Afrilia Zalsabila; Moh. Unis (SOSFILKOM : Jurnal Sosial, Filsafat dan Komunikasi, 2025)
This article analyzes the phenomenon of adopting Korean aesthetic standards in Indonesia as a manifestation of disciplinary power within Michel Foucault's theoretical framework. Through the spread of Korean popular culture (Hallyu), a new regime of truth about the ideal body like white skin, slim figure, and V-line face has been disseminated and internalized. This study argues that beauty practices such as skincare routines, dieting, and consumption of K-beauty products are not free individual choices, but rather forms of self-discipline that produce docile bodies. Using genealogical and discourse analysis, this article traces how this power operates productively through the media, the beauty industry, and fan communities, shaping consumer subjectivity and desire in Indonesia. Furthermore, this analysis examines the biopolitical impact of this phenomenon on mental health and the economics of desire, and explores spaces of resistance to this aesthetic hegemony.